Cytoarchitecture of the Hippocampal Subfields CA3, CA4, and the Dentate Gyrus in Human Cerebrum: A Detailed Histological Analysis - Suvarna Anil Rampelliwar; Anjali Sabnis; Manisha Tambekar (National Journal of Clinical Anatomy)
Background: The hippocampus is a gray matter collection within the medial temporal lobe and plays a vital role in memory and spatial navigation. This study aims to explore the cytoarchitecture of the hippocampal subfields in the cornu ammonis (CA) region, i.e. CA3, CA4, and dentate gyrus, its analysis of the thickness of layers (μ) and cellular dimensions (μ), and analysis of radial glial cells. Methodology: We studied the cytoarchitecture of hippocampal subfields in 21 human cadavers. The research involved detailed histological analysis of hippocampal subfields, i. e., CA3, CA4, and dentate gyrus, using hematoxylin and eosin staining, using ImageJ software to measure the cellular dimensions (μ) and thickness (μ) of each layer and the cells present within each layer. In additionally, immunohistochemical detection of glial fibrillary acidic protein (GFAP) was done to identify radial glial cells. Results: Significant differences in the thickness of hippocampal layers and cell sizes among the subfields were noted. Specifically, CA3 and CA4 subfields exhibit distinct structural features compared to the dentate gyrus, with CA4 showing a variation in layer differentiation. GFAP staining revealed variable expression across samples, reflecting the presence and activity of radial glial cells involved in neurogenesis and neural plasticity. Conclusion: The study enhances the understanding of hippocampal cytoarchitecture and its implications for brain function and neurogenesis.